EVALUATION OF CONSTRUCTION MATERIALS ON PROJECT SITES IN FEDERAL CAPITAL TERRITORY, F.C.T, ABUJA - Micheal, F.; Mahmoud, A.; Ishaya, K.S; Kpalo, S.Y (Engineering Heritage Journal)
Assessment of building construction material on building sites is a function that critically contributes to the achievement of the project goals. Poor construction materials in construction projects sites has many issues which contribute to it such as: wastage of construction materials, and improper handling on site. This work aims to consider the evaluation of construction materials on project sites. Questionnaires from field survey, interview and site observation were the source of data collected. Descriptive statistics including frequency and mean index score method was used for the study. The study reveals that most problems such as conditions of weather, management of excess materials as well as low response from company to site were identified with mean value above the average mean of 3.32. The study also indicated that most wastage, such as: change in design, improper scheduling of work plan, and lack of supervision in usage of materials observed with mean value above the average mean of 3.37. From the results of the study, it was concluded that, most activities on management of construction materials which are challenging that has to do with wastage in building construction project sites and management of construction material, were identified in the study area. Thus, the study recommends that the consultants, contractors, clients and other professionals that work in the building construction industry should upgrade their commitment toward staff training as well as developing the necessary skills needed in the industry.